Suitable Combination Between Beauveria bassiana (Balsamo) Vuillemin and Four Plant Leaf Extracts to Control Spodoptera litura (Fabricius) - Aminudin Afandhi; Vivi Renna Pratiwi; Mochammad Syamsul Hadi; Yogo Setiawan; Retno Dyah Puspitarini (AGRIVITA, Journal of Agricultural Science, 2020)
Lepidopteran pests such as S. litura might cause yield losses in many crops especially during pest outbreak. The combinations of microbial and botanical insecticides were expected to increase the effectivity in controlling the respected insect pest. This research aimed to evaluate the combination of plant extracts and B. bassiana to control S. litura. The compatibility of B. bassiana with different plant extracts such as Neem, Chinaberry, Mexican Sunflower and Lantana leaves was studied in the laboratory. The compatibility was evaluated based on B. bassiana colony growth, conidia density, conidia viability, and mortality of S. litura larvae. After 12 days after application (DAA), colony growth of B. bassiana was reduced by all plant extract treatments. For the mortality of S. litura, the combined mixture of B. bassiana and 0.25% Chinaberry extract resulted the maximum mortality rate (44%). After 12 and 15 DAA, the 0.25% Chinaberry showed the highest colony growth (3.93 and 4.37 cm). The most suitable treatment was B. bassiana with 0.25% Chinaberry that had the conidial density at 1.77 x 108 conidia/ml and conidial viability of 75.63% and can enhanced the mortality of S. litura larvae.